CHALLENGES IN QUALITY IMPROVEMENT OF ENGINEERING EDUCATION IN INDIA - Mishra, Atul (PEOPLE: International Journal of Social Sciences, 2017)
In India, Engineering Education is being implemented under Ministry of Human Resource Development. Factors contributing for the quality of Engineering education are mainly - financial constraints, trained technical teachers, lack of standardization, lack of practical exposure, lack of priority and other factors. The research discusses the initiatives undertaken for quality assurance in engineering education. It identified the need for development and training of technical teachers in imparting knowledge based teaching and learning, redesigning suitable curriculum, use of multiple teaching resources, introducing ICT added teaching and competency based assessment along with others. The rising need for Industry Institute collaboration emerges out for identification of manpower requirement, identification courses, sector-wise skill profile and development of competency based curricula and learning material, competency based training, assessment & joint certification.